Developing a real time taxi monitoring and passenger inventory system in Zimbabwe - Kuri, Emmanuel (Midlands State University, 2017)
The design and implementation of this real time taxi monitoring and Passenger inventory system is meant to unleash a new era of systematic taxi operation in Zimbabwe. It introduces a tight close monitoring environment for taxis so as to maximise on returns from the business. In the prevailing situation where there is a general lack of effective monitoring of taxis the employees run a parallel business of their own using the same taxis. This inherent inefficiency in the system adversely affect turn over. The new system uses GPS and GSM networks to locate and track these taxis and providing numerous selected parameters which the Owner might be interested to know at any given time. An opportunity which qualify this project comes from massive volumes of people who use the public transport system in many parts of the world. The project lends itself to a ready estimated market of more than 10000 taxis operating in Harare alone. The taxi monitoring and Passenger inventory system is empowered to indicate the instantaneous Passenger inventory at any moment so that collected revenue can be matched to the day’s activities. This information will be availed by SMS on the Owner’s cellphone. The system focuses on any public transport system where accountability on the business activities are of primary concern.